Reflection of Pakistani culture and society in the fictions of Mastansir Hussain Tarar - Dr. Sabina Awais; Dr. Ammara Tariq (Zaban-o-Adab, 2022)
Mustansir Hussain Tarrar is a famous writer of Urdu fiction. He is an author, television anchor, tourist, novelist, columnist and short story writer. He focused irritation, disappointment, mental disturbance of the people of Pakistan in his short stories. He discussed the climatic conditions of the region and its effects on animals and birds. Moreover the reader find the changing human culture in different character pf the short stories. Ther character used in his fiction have multidimentional approach and has strong binding with these social and cultural values as depicted in his findings. Tarar has made his short stories more impressive through the modern techniques (like myth). His also take the martial lawa as a subject. All of his fiction. In this article, the reflection of the cultures of Pakistan in his short stories is being discussed.